Kurumsal / ticari bankacılıkta işlem kalitesini yükseltme sürecinde uyulması gerekli prensipler - Babacan, M. Çağatay (My University, 2001)
THE PRINCIPLES TO BE FOLLOWED THROUGH THE PROCESS TOWARDS HIGHER QUALITY AT CORPORATE/ COMMERCIAL BANKING SERVICES This research has stemmed from the fact that despite various attempts for getting quality certificates in formal terms, banking sector has frequently failed during its journey towards ensuring the real quality in its inner meaning. When investigated, it's found that the point is not only to provide formal certificates which are the technical proof of the quality there, but to be able to spread the quality throughout the company in terms of the behaviours of the employees working in all layers of the company and the approaches towards inner and outer customers. The literature on quality focuses on a number of specific concepts that are concerned as indispensable, such as total quality, total quality management, kaizen all of which share a unique terminology being composed of those items as top management involvement, training of employees, focus on clients and team work. In almost all total quality applications it's aimed to prevent extravagancies, improve efficiency, lower costs, shorten transactions periods and consequently achieve continuous betterment and improvement. The concepts of personal and service quality have also been touched upon in our research. Personal quality is discussed as the basis of quality regardless of sector, time, and specific mission to be carried out. Any firm in the process of achieving quality has to ensure the personal quality of employees. In achieving this, it's necessary to create common ideals, values. This requires various procedures such as providing opportunities to employees to self-actualize, to improve themselves which requires continuous training, development of communication within the company, and settlement of team spirit. In the part that service quality is being mentioned, there are comparisons between service and goods in various ways besides the characteristics of the term service. Then comes service industry, what quality means in service sector as different from that of commodity industry. Next to discussion of service industry in general, comes analysis of banking sector in terms of corporate / commercial banking services and what service quality means there. We also mentioned about the gurus of quality and their contributions to development of the concept of quality. During the related part in our research, we tried to present the similarities and differences among them while making comments in terms of subjectivity and objectivity of those theories. It should be stated that the concept of kaizen comes upon in almost every theory related with quality. Kaizen is a Japanese term which means continuous betterment and development of activities in a company. After mentioning about banking activities and theories on quality, we also analized some daily banking activities and the discrepancies from the principles mentioned in those theories mostly stemming from harsh competition going on in the market. There is also a part in which common expectations of bankers are being stated. Those expectations differ in a wide range from betterment of conditions of promotion within bank to putting some rules by the state or a specific institution that ensure certain standards in various activities in banking industry. The second part is the research which has been applied in various branches of 5 different banks and by participation of 97 people working at those branches. In this part, the following 8 specific banking activities is being mentioned in detail; 1.Repurchase agreement 2.Credit allocation from abroad 3.Transfer within the country 4.Collection of taxes 5.Openin a letter of credit 6.Electronic Fund Transfer 7.Fund transfer to abroad 8.Credit approval and allocation In our research, by analizing the frequencies of answers given to each item for each banking operation it was aimed to find the ideal order of steps to be performed for that specific banking operation. That is, for repurchase agreement for instance, the item which gets the highest frequency to be the first step is concluded as the first thing to be done while performing that transaction. The same logic applies for the rest of the items at each banking operation. Then come the findings. In this part, besides giving the findings, some relations with regard to demographic variables have been tried to capture. At the end, the results have been presented in a sort of

. By this, it's aimed to remind the most representative outputs related to each banking operation. It should be said that the economic conditions in Türkiye during the period our research has been carried out were really hard specifically for banking industry. During those years more than 10 banks have been closed by the state. Some banks were acquired by foreign banks while some others have preferred to merge. Those conditions made it hard to reach the relevant personnel in those banks. Many of them were dismissed by the new management. Consequently, some of our questionnaires couldn't be got back. Despite all those limitations, we have completed our research and hope it'll be a starting point
Keywords: Bankacılık